Treatment outcomes of nanoliposomal irinotecan as second-line chemotherapy after gemcitabine and nab-paclitaxel in metastatic and recurrent pancreatic cancer. (16th September 2022) - Mie, Takafumi; Sasaki, Takashi; Okamoto, Takeshi; Takeda, Tsuyoshi; Mori, Chinatsu; Furukawa, Takaaki; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Sasahira, Naoki
Abstract: Background: To compare the treatment outcomes of nanoliposomal-irinotecan (nal-IRI) plus fluorouracil and leucovorin (5-FU/LV) and modified FOLFIRINOX (mFFX) as second-line treatment after gemcitabine with nab-paclitaxel (GnP) for metastatic and recurrent pancreatic cancer. Methods: We retrospectively analyzed consecutive patients with metastatic or recurrent pancreatic cancer treated with nal-IRI plus 5-FU/LV or mFFX after first-line GnP treatment between March 2014 and October 2021 in our hospital. Patient characteristics, treatment outcomes and adverse events were extracted for comparison. Results: Two hundred sixteen patients were included (nal-IRI plus 5-FU/LV/mFFX: 50/166). Patients in the nal-IRI plus 5-FU/LV group were older, had poorer ECOG PS, and a higher rate of peritoneal metastasis than those in the mFFX group. Median overall survival was 9.5 and 9.8 months ( P  = 0.97), respectively, and the median progression-free survival was 4.5 vs 4.8 months ( P  = 0.61), respectively. Anorexia, fatigue and peripheral neuropathy were more common in the mFFX group, but there was no difference in grade 3/4 adverse events between the two groups. Conclusions: There was no significant difference in efficacy between nal-IRI plus 5-FU/LV and mFFX after GnP. Nal-IRI plus 5-FU/LV appears to be a viable alternative to mFFX as second-line treatment after GnP. Abstract : The efficacy of nanoliposomal-irinotecan plus fluorouracil and leucovorin and modified FOLFIRINOX as second-line treatment after gemcitabine with nab-paclitaxel for metastatic and recurrent pancreatic cancer was equivalent.